2020
DOI: 10.1080/22221751.2020.1799721
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors and molecular epidemiology of carbapenem-resistant Klebsiella pneumoniae in patients from Zhejiang, China, 2008–2018

Abstract: Carbapenem-resistant Klebsiella pneumoniae (CRKP) is emerging as a worldwide public health concern; however, the longterm molecular epidemiological surveillance of clinical CRKP in China is limited. We conducted a retrospective observational study (2008-2018) to assess the prevalence, susceptibility, risk factors and molecular epidemiology of clinical CRKP isolates. We found the prevalence of CRKP increased from 2.5%, 2008 to 15.8%, 2018. CRKP were significantly more frequent among hospitalized patients from I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
80
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(108 citation statements)
references
References 29 publications
10
80
3
2
Order By: Relevance
“…This indicates that increasingly serious threats by ST11 are emerging. bla KPC-2 was responsible for the observed resistance in most of the CRKP isolates in the ICU, and is consistent with other reports (Shen et al, 2009;Hu et al, 2020), a typical plasmid-mediated drug resistance gene, that is widely distributed in different sizes and types of plasmids (Jain et al, 2013;Pitout et al, 2015). The success of the conjugation experiment in this study demonstrated the transferability of drug-resistant plasmids.…”
Section: Discussionsupporting
confidence: 91%
“…This indicates that increasingly serious threats by ST11 are emerging. bla KPC-2 was responsible for the observed resistance in most of the CRKP isolates in the ICU, and is consistent with other reports (Shen et al, 2009;Hu et al, 2020), a typical plasmid-mediated drug resistance gene, that is widely distributed in different sizes and types of plasmids (Jain et al, 2013;Pitout et al, 2015). The success of the conjugation experiment in this study demonstrated the transferability of drug-resistant plasmids.…”
Section: Discussionsupporting
confidence: 91%
“…CHINET surveillance showed that the national average CRKP isolation rate in 2019 was 27.6% [13]. The 2014-2018 survey in Zhejiang Province indicated that the CRKP prevalence rate in Shaoxing was 9.72%, the detection rate by our study is slightly higher than that, which is far lower than the national average level [17]. However, the hospitals covered by the above-mentioned research studies are completely different, and there are also certain differences from the six hospitals covered by this research.…”
Section: Discussioncontrasting
confidence: 56%
“…ESBLs genes are mostly mediated by plasmids, which can spread between bacteria, including TEM, OXA, CTX-M, and SHV, etc, among which CTX-M is the main type contribution of the epidemiologic evolution of human ESBL infections [16]. An epidemiological survey in Zhejiang Province shows that the ESBLs rate is slightly higher than 20% in recent years [17]. The results in 2019 in the Shaoxing region are consistent with it.…”
Section: Discussionmentioning
confidence: 79%
“…Notably, this rate was higher than that recorded in adults. 11 , 13 , 22 CRKP is resistant to most antimicrobial drugs and there are currently limited therapeutic options available, making infections difficult to control and resulting in high mortality rates. 12 , 13 The main mechanism of CRKP resistance is the production of enzymes, such as carbapenemases, ESBLs and AmpC, that hydrolyze antimicrobial drugs.…”
Section: Discussionmentioning
confidence: 99%